Beyond Privatizations:: Proposal of a Model to Urban Mobility under the Perspective of the Austrian School of Economics - Paranaiba, Adriano (2015)
The aim of this paper is to propose a funding model and management of urban mobility that gives priority to the participation of the private sector rather of government action, which comes in Brazil, demonstrating inefficient. To do so, has chosen up the analysis of the Austrian school of economics concerning regulation of public goods to serve as a basis to propose a method that overcomes the concessions and public-private partnerships. The model proposes greater involvement of property owners can contribute to gains in real estate values, supporting for revenue generation for system maintenance.